Randomized clinical trial of open suture repair versus totally extraperitoneal repair for treatment of sportsman's hernia - Sheen, Aali J.; Montgomery, A.; Simon, Thomas; Ilves, I.; Paajanen, H. (The British journal of surgery, 2019)
Background Sportsman's hernia/athletic pubalgia is a recognized cause of chronic groin pain in athletes. Both open and laparoscopic surgical repairs have been described for treatment, but there are no comparative studies. The hypothesis here was that relief of pain would be achieved earlier in patients treated with open minimal suture repair than totally extraperitoneal repair. Methods A randomized multicentre trial in four European countries was conducted to compare open minimal suture repair with totally extraperitoneal repair. The primary endpoint was complete relief of pain (visual analogue scale (VAS) score 20 or less on a scale from 0 to 100 mm) at 1 month. Secondary endpoints included complications, time to return to sporting activity, and number of patients returning to sport within 1 year. Results A total of 65 athletes (92 per cent men) with a median age of 29 years were enrolled (31 open repair, 34 totally extraperitoneal repair). By 4 weeks after surgery, median preoperative VAS scores had dropped from 70-80 to 10-20 in both groups (P < 0·001). Relief of pain (VAS score 20 or less) during sports activity 4 weeks after surgery was achieved in 14 of 31 patients after open repair and 24 of 34 after totally extraperitoneal repair (P = 0·047). Return to full sporting activity was achieved by 16 and 18 patients respectively after 1 month (P = 0·992), and by 25 versus 31 after 3 months (P = 0·408). Conclusion Totally extraperitoneal repair was less painful than open repair in the first month, but otherwise both procedures were similarly effective in treating chronic pain due to sportsman's hernia. Registration number: NCT02297711 ( http://www.clinical.trials.gov).
Gesehen am 04.02.2020